Chain of rings: a radiographic sign of papillary thyroid cancer. Issue 2 (April 2015) - Juan, Y.-H.; Hsuan, H.-F.; Ng, K.-K.; Ng, S.-H.; Yu, C.-W.; Liu, H.; Lin, Y.-C.
Abstract : Papillary thyroid cancer is the most common form of thyroid malignancy in children and adult with frequent metastases to the cervical lymph nodes. We present a case of metastatic papillary thyroid cancer with remarkable imaging findings of consecutive metastatic calcified lymph nodes resembling a chain of rings. While accompanying by a coarsely calcified thyroid mass, possible thyroid cancer should be considered and serve as a guide to warrant further thyroid cancer evaluation.